2017
DOI: 10.1002/ctpp.201500142
|View full text |Cite
|
Sign up to set email alerts
|

Transverse motion of a plasma column in a sheet plasma

Abstract: In this paper, we show the dynamic behaviors of a sheet plasma and the corresponding release of blob-like plasmas to the periphery of the sheet based on observation with a high-speed camera. We found that the plasma column moves in a transverse direction reciprocally when injecting a small amount of Ar gas to the He plasma from the plasma source region. The motion continued periodically at a frequency of ∼5 kHz. The frequency of the plasma column motion decreased with increasing Ar gas flow rate and increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Figure 6 (b) shows the temporal evolution of wavelet spectrum. Previously, blob-like phenomena were observed in a similar linear device TPD-Sheet IV [6], where the blowoffs occur periodically. Different from TPD-Sheet IV, the phenomena were intermittent in NAGDIS-II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 (b) shows the temporal evolution of wavelet spectrum. Previously, blob-like phenomena were observed in a similar linear device TPD-Sheet IV [6], where the blowoffs occur periodically. Different from TPD-Sheet IV, the phenomena were intermittent in NAGDIS-II.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma blob has a filamentary structure along the magnetic field line and has a higher density than the SOL plasma. Interestingly, the cross-filed plasma transport, which could be associated with plasma blob-like structure, was found to be enhanced in the detached plasma condition in linear plasma devices [4][5][6], helical devices [7], and tokamaks [8,9]. In the linear plasma device NAGDIS-II (NAGoya DIvertor plasma Simulator II), fast framing camera observations have revealed that a spiral structure ejected from the plasma column was rotated in E × B direction in the peripheral region of the plasma column, where the electric field was in the radial direction [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…In magnetic confinement fusion devices, plasma detachment based on the interaction between the plasma and neutral particles is a promising way to reduce the heat load on the divertor plate. In the detached divertor condition, an enhancement of the cross-field plasma transport is observed in several magnetic confinement devices including torus [1,2,3,4,5] and linear plasma devices [6,7,8,9,10,11]. In linear device NAGDIS-II, the enhanced transport was found to be generated locally along the magnetic field lines [12,9], and the region was identified to be near the highly volume-recombining region, called the "recombination front" [13].…”
Section: Introductionmentioning
confidence: 99%
“…In cylindrical magnetized plasmas, intermittent density fluctuations were observed. Blobs or intermittent radial transport in PISCES-A, 12,13) NAGDIS-II, 14,15) ULS, 16) LAPD, 17) and TPD-Sheet IV 18) emerged on the surface of cylindrical plasma with arc discharge sources. Similar phenomena were also observed in RF plasma sources, PANTA, 19) VINETA 20,21) and in the loss-cone of the GAMMA10/PDX mirror machine.…”
Section: Introductionmentioning
confidence: 99%